Age estimation based on pulpal changes in 14 – 25 years old. - Ismail, Izzati Nabilah Ismail; Khamis, Mohd Fadhli Khamis (University Sains Malaysia ( USM), 2009)
Secondary dentin formation is a slow continuous process that occurs following completion of dental development which leads to a continuous decrease in the size of pulp cavity. Changes in the pulp size of young permanent teeth with completed root formation provide an alternative and additional biomarker for age estimation. This study was conducted to explore the association between pulp size and chronological age in Malay young adults with respect to different sides and sex. Orthopantomograms of 165 healthy Malay males and females each with an age ranging from 14 to 24 years old were used. Pulpal changes were evaluated by calculating the ratios of measured length and width of tooth and root of mandibular canines: the pulp/root width at three levels i.e. root and pulp width at CEJ level (A), root and pulp width midway between measurements A and C (B); and root and pulp width midway between apex and CEJ(C). The ratios were measured using Vixwin Pro 2000 version 1.5. Pulp changes between the right and left canines were tested using paired t-test and showed bilateralism trend. A multiple regression analysis indicated that sex and tooth ratios did not make significant contribution to the prediction of age. This study illustrates the symmetrical trend and lack of sexual dimorphism of pulp changes with weak correlation between pulpal size and chronological age in Malay young adults.